2008
DOI: 10.1111/j.1365-2605.2007.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Splenic cytokines in mice immunized with testicular germ cells

Abstract: We previously established that two subcutaneous injections of viable syngeneic testicular germ cells (TGC) alone can induce CD4+ T cell-dependent experimental autoimmune orchitis (EAO) in mice. This model is histologically characterized by lymphocytic infiltration into the testes and the following aspermatogenesis. In the present study, we investigated the dynamics of splenic cytokines in EAO, using specific enzyme-linked immunosorbent assay. We found that splenic production of both type 1 helper T cell (Th1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In the present study, a significant increase of testicular IL-6 mRNA expression was not detected. This is an unexpected results, because IL-6, a cytokine that activates B lymphocytes and promotes development of antibody production, was significantly secreted by splenic lymphocytes isolated from TGC-immunized mice [12,18]; furthermore, significant numbers of B lymphocytes and plasma cells were found in EAO lesions with the production of serum autoantibodies [33,34]. This discrepancy between testicular and splenic IL-6 indicates that intratesticular Th1 immune responses are critical during EAO lesions and that systemic Th2 responses outside the testis affect infiltration of lymphocytes of B cell lineage into the testis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the present study, a significant increase of testicular IL-6 mRNA expression was not detected. This is an unexpected results, because IL-6, a cytokine that activates B lymphocytes and promotes development of antibody production, was significantly secreted by splenic lymphocytes isolated from TGC-immunized mice [12,18]; furthermore, significant numbers of B lymphocytes and plasma cells were found in EAO lesions with the production of serum autoantibodies [33,34]. This discrepancy between testicular and splenic IL-6 indicates that intratesticular Th1 immune responses are critical during EAO lesions and that systemic Th2 responses outside the testis affect infiltration of lymphocytes of B cell lineage into the testis.…”
Section: Discussionmentioning
confidence: 85%
“…Both IFN-γ and TNF-α were detected from cultured spleen cells and lymph node cells in EAO-induced mice in vitro [12,18]. Through in vivo studies, the effects of these two cytokines were investigated by administration of anti-IFN-γ and anti-TNF-α monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In EAO, adeno-associated virus-mediated human IL-10 gene transfer suppressed the development of the disease ( Watanabe et al 2005). However, it exerts the opposite effect in some autoimmune diseases including EAO (Rosenbaum & Angell 1995, Hill & Sarvertnick 2002, Kaneko et al 2003, Tokunaga et al 2008. Although pathophysiological effects of these two cytokines on the epididymal tissues remain unclear, the Vx-induced elevation of the epididymal cytokines may attract inflammatory cells to the epididymis rather than the testis.…”
Section: Effects Of Vasectomy On Testicular Autoimmunitymentioning
confidence: 99%
“…We previously demonstrated that immunization of C3H/He and A/J mice with viable syngeneic testicular germ cells (TGC) alone induces EAO without an adjuvant (Itoh et al 1991a, 1991b, Tokunaga et al 2008. However, this EAO model is very unique in which orchitis can occur without epididymitis.…”
Section: Introductionmentioning
confidence: 99%